2017
DOI: 10.1007/s11060-017-2649-8
|View full text |Cite
|
Sign up to set email alerts
|

Local alkylating chemotherapy applied immediately after 5-ALA guided resection of glioblastoma does not provide additional benefit

Abstract: Grade IV glioma is the most common and aggressive primary brain tumour. Gross total resection with 5-aminolevulinic acid (5-ALA) guided surgery combined with local chemotherapy (carmustine wafers) is an attractive treatment strategy in these patients. No previous studies have examined the benefit carmustine wafers in a treatment programme of 5-ALA guided resection followed by a temozolomide-based chemoradiotherapy protocol. The objective of this study was to examine the benefit of carmustine wafers on survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…Since 2005, one pivotal clinical trial defined the radiotherapy and temozolomide combination (RT–temozolomide) as the standard of care in patients with newly-diagnosed GBM, for patients 18–70 years old with a WHO performance status of ≤ 2 [ 6 ]. Carmustine wafer (CW) is an option when maximal safe resection (RS) is performed and high grade glioma is histologically proven [ 11 14 ]. More recently, bevacizumab in combination with RT–temozolomide in first-line treatment showed a significant prolonged progression-free survival but failed to demonstrate a significant overall survival (OS) benefit [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2005, one pivotal clinical trial defined the radiotherapy and temozolomide combination (RT–temozolomide) as the standard of care in patients with newly-diagnosed GBM, for patients 18–70 years old with a WHO performance status of ≤ 2 [ 6 ]. Carmustine wafer (CW) is an option when maximal safe resection (RS) is performed and high grade glioma is histologically proven [ 11 14 ]. More recently, bevacizumab in combination with RT–temozolomide in first-line treatment showed a significant prolonged progression-free survival but failed to demonstrate a significant overall survival (OS) benefit [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the other three RCTs, implantation of carmustine was not randomized and was decided according to clinical conditions (6,20,21). The comparability of one cohort study is obscure (22), while that of others is relatively distinct (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The results of the methodological quality assessment using NOS and Jadad scale are also shown in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Next, we investigated whether the addition of carmustine therapy as a supplement to STUPP protocol could confer more significant survival benefits for GBM patients. There were only two studies that reported the comparison of survival benefits between patients with TMZ chemotherapy and TMZ plus carmustine chemotherapy (25,33). The analysis of the two studies showed that GBM patients receiving combined chemotherapy (carmustine plus TMZ) had longer OS than those receiving TMZ alone (HR = 0.78, 95% CI = 0.63-0.97, P = 0.02, I 2 = 0%) ( Figure 3C).…”
Section: Association Between Carmustine Treatment and Survival Of Glimentioning
confidence: 99%
“…While the clinical benefits of BCNU wafers have not greatly ameliorated the tumor burden in GB patients, an abundance of clinical literature using this adjuvant therapy provides key and quantitative lessons for the next generation of local chemotherapy delivery systems. In the development of the underlying material of the wafer technology, a motivational principle was the sustained local delivery of a high chemotherapy concentration within the pharmaceutical window as an adjuvant therapy .…”
Section: Outcomes and Lessons From The Clinicmentioning
confidence: 99%